Experimental study of the instabilities observed in 650 V enhancement mode GaN HEMT during short circuit. (September 2017) - Abbate, C.; Busatto, G.; Sanseverino, A.; Tedesco, D.; Velardi, F.
Abstract: The paper presents the results of an experimental analysis of the short circuit behaviour of 650 V GaN power HEMT. It is shown that the DUTs exhibit two kinds of failure. A first failure mode involves large dissipated energies and can be attributed directly to the increase of the local temperature in the device. The second failure mode is less attributable to local thermal increase and it is proposed that it is associated with instabilities due to charge-field phenomena taking place in the device at high voltage. The paper shows that 650 V GaN power HEMTs are affected by high frequency oscillations which appear in the SC waveforms as it happens in the short circuit of the IGBTs. Highlight: Experimental tests have shown that 650 V GaN power HEMTs exhibit two kinds of failures when operated in short circuit. First failure mode involves large dissipated energy and can be attributed to the increase of internal device temperature. Second failure mode is associated with charge-field phenomena taking place in SC due to high voltage and current density. 650 V GaN power HEMTs can be affected by high frequency oscillations when operated in SC in presence of capacitive drivers. Oscillations can be attributed to a positive feedback appearing in the range 75 – 85 MHz due to gate drain capacitance.